Penyelesaian Tindak Pidana Penganiayaan Melalui Pendekatan Restorative Justice (Studi Kasus di Desa Mohiyolo) - Potabuga, Alvareza; Ismail, Dian Ekawaty; Y., Avelia Rahmah (Journal Evidence Of Law, 2025)
This study aims to examine how criminal acts of assault are resolved through the Restorative Justice approach in areas located far from police stations as centers for reporting and complaints, as well as to analyze the role of the village government as a Restorative Justice House in providing justice for the community in Mohiyolo Village, Asparaga District, Gorontalo Regency. The approach applied uses a descriptive qualitative method, with data collection through interviews, observations, and documentation. The findings show that restorative settlement in the village involves the perpetrator, victim, their families, community leaders, and village officials as mediators. The geographical distance from the police station encourages the community to resolve disputes through village deliberations that prioritize the principles of justice, utility, and social harmony. The effectiveness of this approach is demonstrated by a yearly decline in reported cases. The village government acts as a Restorative Justice House that facilitates peaceful, swift, and efficient case resolution. This study recommends strengthening regulations and the role of village governments to support the sustainability of restorative justice as an alternative to the formal criminal justice system.